Analysis of the closure of underground mining operations to achieve environmental protection: the Mimosa case - De la Cruz Carrasco, Estanislao (2004)
In the Buenaventura S.A. Mining Companys Mimosa Mine - Julcany Unit - the main problem is the presence of acid waters in underground work, earthwork yards and tailings yards that pollute water, soil, flora and fauna sources. In order to mitigate this situation, the three main sources of pollution would have to be controlled. With such a purpose the company has developed environmental management and adequation programs, comprehending: The closing of mine entrances, chimneys and open pits, to avoid air and water coming into underground work, the construction of cunetas de coronación1 to avoid leaching through earthwork and tailings yards, the separation of neutral and acid waters inside the mine, and the capsulling of earthwork and tailings yards. An analysis is made from each closing activity and suitable solutions are recommended.